Hercules 265 rapid response: Immediate ecosystem impacts of a natural gas blowout incident. (July 2016) - Weber, Sarah C.; Peterson, Leigha; Battles, Jessica J.; Roberts, Brian J.; Peterson, Richard N.; Hollander, David J.; Chanton, Jeffrey P.; Joye, Samantha B.; Montoya, Joseph P.
Abstract: In late July 2013, the Hercules 265 drilling rig in the Northern Gulf of Mexico experienced a catastrophic loss of control. Large quantities of natural gas spewed into the environment for 2 days before the well self-sealed through down-hole collapse below the seafloor. Ecosystem Impacts of Oil and Gas Inputs to the Gulf (ECOGIG) and collaborating Gulf of Mexico Research Initiative (GoMRI) consortia mounted a rapid response cruise to characterize the waters around the Hercules 265 rig, beginning just 4 days after the blowout. Our analysis showed an immediate microbial response to the elevated concentrations of methane in the water column, as evidenced by the drawdown of oxygen to hypoxic conditions, the incorporation of methane-derived carbon into particles, and measurable rates of methane-assimilation and nitrogen-fixation. Additionally, radium isotope measurements allowed us to constrain the timescale of bottom water exposure to the influence of the rig. A second sampling by the Center for Integrated Modeling and Analysis of Gulf Ecosystems (C-IMAGE) consortium indicated that the ecosystem had returned to near pre-blowout conditions within one month.